A New Approach to Modeling Sector Stock Returns in China. Issue 5 (3rd September 2017) - Chong, Terence Tai-Leung; Li, Nasha; Zou, Lin
Abstract : This article analyzes the relationship between excess stock returns and the macroeconomy of China. A factor-augmented regression is applied to a panel of 123 monthly Chinese macroeconomic time series. Eight fundamental macroeconomic factors are identified and used to examine the excess returns in industrial, commercial, real estate, and utilities sectors of the market. It is found that interest rate, output level, as well as property supply factors possess explanatory power for sector stock returns in China.